Are adipocytokines inflammatory or metabolic mediators in patients with inflammatory bowel disease? - Kahraman R; Calhan T; Sahin A; Ozdil K; Caliskan Z; Bireller ES; Cakmakoglu B (Dove Medical Press, 2017)
Resul Kahraman,1 Turan Calhan,1 Abdurrahman Sahin,1 Kamil Ozdil,1 Zuhal Caliskan,1 Elif Sinem Bireller,2 Bedia Cakmakoglu3 1Department of Gastroenterology, Umraniye Education and Training Hospital, Health Sciences University, 2Department of Pharmaceutical Microbiology, Faculty of Pharmacy, Istanbul Yeni Yuzyil University, 3Department of Molecular Medicine, Aziz Sancar Institute of Experimental Medicine, Istanbul University, Istanbul, Turkey Abstract: This study examined the adiponectin and leptin levels and insulin resistance (IR) in patients with inflammatory bowel disease (IBD) and the associations between these factors and IBD characteristics. Fasting serum leptin, adiponectin, glucose, and insulin levels, as well as inflammatory parameters, were measured in 105 patients with IBD (49 patients with Crohn’s disease [CD], 56 patients with ulcerative colitis [UC]) and 98 healthy controls [HC]. IR was evaluated using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Disease activity and severity in patients with UC were evaluated using the Truelove–Witts index, and patients with CD were evaluated using the Crohn’s Disease Activity Index. Serum adiponectin levels were found to be significantly lower in patients with CD and UC (p<0.001). Serum leptin levels were also found to be significantly higher in both the UC and CD groups (p<0.001). When HOMA-IR levels were compared, no significant difference was detected for either the CD or UC groups compared with the controls. In conclusion, it was shown that leptin levels increased and adiponectin levels decreased in patients with IBD, which is thought to be related to chronic inflammation. The effects of adipocytokines in patients with IBD with inflammatory and metabolic processes need to be investigated in further broader studies. Keywords: ulcerative colitis, Crohn’s disease, insulin resistance, adiponectin, leptin